Alligator bites never heal [compact disc] - Doechii, 1998- (Top Dawg Entertainment, 2025)
"With her Grammy Award-winning mixtape, rapper, singer and visionary artist Doechii delivers nineteen tracks following the weekly "Swamp Session" installments that lit the internet on fire with eye-catching visuals and equally compelling bars. The Best Rap Album-winning project, featuring "Denial Is A River' and 'Nissan Altima," captures a rare talent in her rawest form yet giving listeners distinct windows into her one-of-a- kind artistry." --www.cvsmidwesttape.ca.